IMPLEMENTASI SELF-REGULATED LEARNING DALAM PEMBELAJARAN MATEMATIKA - Ayu Wulandari, Siti; Farda Nugroho, Yogi; Kusno, Kusno (Jurnal Inovasi dan Teknologi Pendidikan, 2026)
Self-regulated learning (SRL) is an individual's ability to manage their learning process independently through planning, monitoring, controlling motivation, and evaluating learning outcomes. This ability is considered important in mathematics learning because it plays a role in improving students' problem-solving skills. This article aims to systematically review previous research results related to the implementation of self-regulated learning in learning, particularly in improving mathematical problem-solving skills. The method used is a literature study by reviewing various relevant scientific articles published in the last fifteen years. The results of the study show that the consistent application of SRL can improve students' learning independence, intrinsic motivation, metacognitive skills, and mathematical problem-solving abilities. The success of SRL implementation is influenced by internal factors, such as motivation and self-efficacy, as well as external factors, such as the role of teachers, the learning environment, and the use of technology. Therefore, well-planned learning strategies and a conducive learning environment are needed so that the implementation of self-regulated learning can run optimally and sustainably.